Efektivitas Pijat Bayi Menggunakan Minyak Kelapa Murni (Virgin Coconut Oil) Terhadap Peningkatan Berat Badan Bayi 1-6 Bulan Di Desa Jenggrong Ranuyoso Lumajang - Hafidah, Nurul; Sary, Yessy Nur Endah; Hidayati, Tutik (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Weight gain is one indicator of infant health that can be used as a measure of infant growth. One of the recommended weight stimulations is baby massage. Baby massage, also known as tactile stimulation, is an art of healthcare and medicine that has been practiced for centuries. Infant massage, among others, can stimulate the digestion of the hormone’s insulin and gasoline, so that food absorption is better. This study aims to determine the effectiveness of baby massage using virgin coconut oil on increasing infant weight for 1-6 months. This study was a pre-experimental design type one group pretest-posttest. The population in this study was infants 1-6 months in the village of Jenggrong Ranuyoso Lumajang involving as many as 40 participants. The sampling technique used is purposive sampling. Data was collected using a data collection sheet. Data were analyzed using Predictive Analytics SoftWare Version 18 with paired sample t-test at the significance level of <0.05. The results showed that the average body weight of children before baby massage was 5174.5 grams (SD ± 1097.6) and the average weight of children after baby massage was 5242.5 grams (SD ± 1077.3). Statistical analysis showed that there was a significant difference in baby weight 1-6 months before and after baby massage using virgin coconut oil (p-value: 0.000) Infant massage is a reasonably simple intervention that effectively raises the baby's weight and benefits both the baby and the parents. To foster parent-child interaction and involve parents in their child's care, specially trained midwives can teach parents how to massage their infants.